The Bahasa Melayu version of the nursing stress scale among nurses: a reliability study in Malaysia - Rosnawati, M.R.; Moe, H.; Masilamani, R.; Darus, A. (SAGE Publications, 2010)
The Nursing Stress Scale (NSS) has been shown to be a valid and reliable instrument to assess occupational stressors among nurses. The NSS, which was previously used in the English version, was translated and back-translated into Bahasa Melayu. This study was conducted to assess the reliability of the Bahasa Melayu version of the NSS among nurses for future studies in this country. The reliability of the NSS was assessed after its readministration to 30 nurses with a 2-week interval. The Spearman coefficient was calculated to assess its stability. The internal consistency was measured through 4 measures: Cronbach's alpha, Spearman-Brown, Guttman split-half, and standardized item a coefficients. The total response rate was 70. Test-retest reliability showed remarkable stability (Spearman's rho exceeded .70). All 4 measures of internal consistency among items indicated a satisfactory level (coefficients in the range of .68 to .87). In conclusion, the Bahasa Melayu version of the NSS is a reliable and useful instrument for measuring the possible stressors at the workplace among nurses.